Empirical analysis of socioeconomic factors determining depression in Brazil - Pauli, Dayane Rocha de; Bruning, Camila; Guimarães, Raquel Rangel de Meireles (Revista PsicoFAE: Pluralidades em Saúde Mental, 2019)
This article investigates empirically possible determinants of the incidence of depression, as a mood disorder, in Brazil. We analyze the impact of socioeconomic factors, focusing on the laboral context, such as occupation and economic activity. To do so, we performed a model of discrete responses called logit, in which we used procedures of complex samples to compare the impacts on depression in two Brazilian databases: the 2008 National Household Sample Survey (Pnad) and the National Health Research (PNS) 2013.